Vietnam's trade liberalization and accession to the WTO - Vu, Hoa Van (KDI School, 2000)
The doi moi (renovation policy) that Vietnam adopted in the late 1980s has led to high growth and more openness in the economy. However, for fur ther sustainable development of the country, Vietnam should accelerate the pace of integration into the world economy, and becoming the member of WTO is an important step for Vietnam in this integration process. The purpose of this thesis is aimed at (i) understanding the WTO principles and agreements and based on that to draw implications for Vietnam’s trade liberalization; (ii) finding the answer for the question why the accession process is so time-consuming, what accession procedures are required, especially for a country in transition like Vietnam; and (iii) Reviewing what Vietnam has achieved in trade liberalization process and what are the challenges/problems remained to be solved with a view to become a WTO member; and (iv) Proposing relevant conclusions and recommendations for Vietnam’s further trade liberalization and WTO accession.
Thesis(Master) --KDI School:Master of Public Policy,2000